ANALISIS DAN KRITIK METODE HERMENEUTIKA AL-QUR’AN MUḤAMMAD SHAḤRŪR - Tarlam, Alam (STAIN Kediri, 2015)
Muḥammad Shaḥrūr is one of the leading contemporary Muslim scholars who criticized the methodology of Qur’anic exegesis as developed by the classical Muslim exegetes. They said that those classical Muslim interpreters treated the Qur’anic textes in a passive and rigid manner, putting them out of the dialecticalcontext and contextualization. Consequently, understanding of the Qur’an is ad hoc and partial. To overcome this problem, Shaḥrūr suggested a new method, approach, and procedure of reading the Qur’an. This paper will critically examine Shaḥrūr’s hermeneutical approach as a new method of reading the Qur’an and otherreligious textes.Keywords: Muḥammad Shaḥrūr, Hermeneutika al-Qur’an, Kontekstualisasi